Pengaruh Human Relation, Leadership Dan TrainingTerhadap Produktivitas Karyawan (Studi Kasus Pada Karyawan PT. Berkat Manunggal Jaya Di Semarang) - Handayani, Woro Dwi; , Imron Rosyadi,S.E.,M.Si (2017)
This study aims to identify and empirically examine (1) the impact of human relations on the productivity of employees. (2) the effect of leadership on employee productivity. (3) the impact of training on employee productivity. (4) the effect of human relations, leadership, and training simultaneously on the productivity of employees at PT.Berkat Manunggal Jaya Semarang. This type of research is quantitative. The sample in this study were employees PT.Berkat Manunggal Jaya Semarang 100 respondents by random sampling sampling techniques. Methods of data collection using questionnaires. Data analysis techniques is multiple regression analysis, t-test, F test, and the coefficient of determination (R2). The results showed a partial effect between the independent variable on the dependent variable. F-test data analysis finds that there are variables simultaneously influence human relations, leadership, and training on employee productivity. While the regression coefficient indicates that the variable human relations more dominant influence of the leadership and training on employee productivity.